Design and implementation of a prototype web-accessible online catalog for the U.P. Main Library using an existing CDS/ISIS database - Saguban, Angie A.; Uy, Mark Benedict O. (2000)
This study aimed to determine the University of the Philippines (UP) Diliman Main Library on-line public access catalog (OPAC) users' profile, user evaluation of the existing OPAC, OPAC features, users' and library staff needs/desires, and fields/features permissible on a web-accessible OPAC. Based on these information, the researchers designed and implemented a prototype accessible OPAC that caters to the needs of the Main Library using the existing Micro-CDS/ISIS software and PERL programming language.